THE CORRELATION OF «THE RIGHT TO HOUSING» AND «HOUSING RIGHTS» DEFINITIONS TO THE LEGISLATION OF UKRAINE - Кармазь, Александра (Modern engineering and innovative technologies, 2017)
The work carried out a scientific analysis of the concepts of "right to housing" and "housing rights". It has been established that "the right to housing" and "housing law" are different concepts. It is proved that the citizens' exercise of the constituti